Effects of copper sources (copper sulfate and Mintrex Cu) on growth performance, carcass characteristics, barn cleaning, and economics in finishing pigs - Kyle F Coble; Joel M DeRouchey; Michael D Tokach; Steven S Dritz; B V Lawrence; J Escobar; Jason C Woodworth; Robert D Goodband; N Boettger (Kansas Agricultural Experiment Station Research Reports, 2014)
A total of 1,196 mixed-sex pigs (PIC 337 × 1050, initially 56.7 lb) were used in a 111-d study. Pens of pigs were allotted to 1 of 6 dietary treatments in a randomized incomplete block design, with 26 pigs per pen (similar number of barrows and gilts) and 7 to 8 pens per treatment. All diets contained 17 ppm copper from copper sulfate (CuSO4) in the premix and were formulated on a standardized ileal digestible (SID) lysine basis at 0.05% below the estimated requirement of the average pig weight during each feeding phase. Treatments included a control diet with no added Cu, diets with either 50 ppm of added Cu from CuSO4 or Mintrex Cu (Novus International, Inc., St. Charles, MO), or 125 ppm of added Cu from CuSO4. The diet containing 50 ppm of Cu from Mintrex Cu and the diet with 125 ppm of Cu from CuSO4 were fed for either the first half of the finishing period (d 0 to 42), at which time they were switched to the control diet, or for the entire duration of the finishing period (d 0 to 111). Overall (d 0 to 111), ADG did not differ among treatments; however, pigs fed either 50 or 125 ppm of Cu from CuSO4 throughout the study had greater ADFI (P<0.05) than pigs fed either the control or diet with 50 ppm of added Cu from Mintrex Cu fed only in early finishing. As a result, F/G was poorer (P<0.05) for pigs fed either 50 or 125 ppm of added Cu from CuSO4 fed continuously compared with those fed 50 ppm of Cu from Mintrex Cu only in early finishing. Manure texture, and more importantly, pen wash time, did not differ among treatments, but manure buildup was 1.44 times more likely (P<0.05) to occur in pens where pigs were fed 125 ppm of added Cu from CuSO4 for the first 42 d of the finishing period compared with those fed no added Cu. For carcass characteristics, pigs fed 50 ppm of Cu from Mintrex Cu in early finishing had reduced backfat (P<0.05) compared with pigs fed the control or 50 ppm of added Cu from CuSO4 or Mintrex Cu throughout the study. For economics, pigs fed 50 ppm of Cu from CuSO4 throughout the study had a higher (P<0.05) total feed cost than the control and diets with 125 ppm of added Cu from CuSO4 fed in early finishing, and 50 ppm of added Cu from Mintrex Cu fed for the first 42 d. Cost per pound of gain was higher (P<0.05) for pigs fed 50 or 125 ppm of Cu from CuSO4 for the entire study than for pigs fed the control diet or the diet with 50 ppm of added Cu from Mintrex Cu fed for the first 42 d, with pigs fed the other diets having intermediate responses. No differences were detected in either carcass gain value or IOFC among treatments. In summary, pigs fed 50 ppm of Cu from Mintrex Cu for the first 42 d of the finishing period had a better F/G compared with pigs fed 50 or 125 ppm of added Cu from CuSO4 for the complete finishing period, but more research is needed to fully elucidate the appropriate source, level, and duration of feeding Cu to maximize growth performance and economic return.; Swine Day, Manhattan, KS, November 20, 2014
Keywords: Swine Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-155-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1110; Finishing pig; Copper; Wash time